Meningkatkan kemampuan mengenal pecahan pada anak tunagrahita melalui metode Guided Discovery - Sari, Sri Riska Ade Permana; Nurhastuti, Nurhastuti; Fitriani, Fitriani (Piramida Akademi, 2024)
This research is motivated by the issues in SLB N 1 Padang concerning students in class VIII C who have low learning outcomes in understanding fractions. The assessment results found that students have difficulty understanding fractions, thus requiring a method to teach fractions, namely the Guided Learning method. This research aims to improve the process and learning outcomes of understanding fractions through the Guided Learning Method. The research method used is Classroom Action Research with qualitative data analysis. This research was conducted at SLBN 1 Padang with subjects being intellectually disabled children totaling 4 students in class VIII C. Based on the research results, the Guided Learning Method can improve the ability to understand fractions. This is evident from the increased learning outcomes of students in each cycle. This guided learning method could increase participation in learning and help students understand the material well because the teacher guides them at each stage of learning.